LncRNA HOXA11‐AS regulates calcium oxalate crystal–induced renal inflammation via miR‐124‐3p/MCP‐1. Issue 1 (3rd November 2019) - Li, Yinhui; Yan, Guiling; Zhang, Jie; Chen, Wei; Ding, Tao; Yin, Yupeng; Li, Minghan; Zhu, Yiqing; Sun, Shuhan; Yuan, Ji Hang; Guo, Zhiyong
Abstract: Long noncoding RNA (lncRNA) has been suggested to play an important role in a variety of diseases over the past decade. In a previous study, we identified a novel lncRNA, termed HOXA11‐AS, which was significantly up‐regulated in calcium oxalate (CaOx) nephrolithiasis. However, the biological function of HOXA11‐AS in CaOx nephrolithiasis remains poorly defined. Here, we demonstrated that HOXA11‐AS was significantly up‐regulated in CaOx nephrolithiasis both in vivo and in vitro. Gain‐/loss‐of‐function studies revealed that HOXA11‐AS inhibited proliferation, promoted apoptosis and aggravated cellular damage in HK‐2 cells exposed to calcium oxalate monohydrate (COM). Further investigations showed that HOXA11‐AS regulated monocyte chemotactic protein 1 (MCP‐1) expression in HK‐2 cell model of CaOx nephrolithiasis. In addition, online bioinformatics analysis and dual‐luciferase reporter assay results showed that miR‐124‐3p directly bound to HOXA11‐AS and the 3'UTR of MCP‐1. Furthermore, rescue experiment results revealed that HOXA11‐AS functioned as a competing endogenous RNA to regulate MCP‐1 expression through sponging miR‐124‐3p and that overexpression of miR‐124‐3p restored the inhibitory effect of proliferation, promotion effects of apoptosis and cell damage induced by HOXA11‐AS overexpression. Taken together, HOXA11‐AS mediated CaOx crystal–induced renal inflammation via the miR‐124‐3p/MCP‐1 axis, and this outcome may provide a good potential therapeutic target for nephrolithiasis.